2022
DOI: 10.21203/rs.3.rs-2167465/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chlorpheniramine Intranasal Spray to Accelerate COVID-19 Clinical Recovery in an Outpatient Setting: The ACCROS Trials

Abstract: Purpose: Our group demonstrated the safety, efficacy, and antiviral effect of intranasally administered Chlorpheniramine Maleate (CPM) for treating coronavirus disease 2019 (COVID-19). Since the nasal cavity is the portal of entry for COVID pathogens, sensory and upper respiratory symptoms (URS) (e.g., cough, ageusia, anosmia, nasal congestion, etc.) are significant symptoms in the course of the disease. Intranasal therapies could alleviate the disease-induced URS faster. This study evaluated the effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Clinical studies have shown that CPM improves clinical recovery and prevents hospitalizations in patients with COVID-19 (Black, 2022;Morán Blanco et al, 2021;Sanchez-Gonzalez et al, 2022). In a two-part clinical study conducted by our team, ACCROS-I, and ACCROS-II, suggested that CPM intranasal-administered is an effective early intervention to reduce symptoms and accelerate clinical recovery in COVID-19 patients (Valerio-Pascua et al, 2022). Results showed that there were less hospitalization and severe cases.…”
Section: Molecular Docking Studiesmentioning
confidence: 90%
“…Clinical studies have shown that CPM improves clinical recovery and prevents hospitalizations in patients with COVID-19 (Black, 2022;Morán Blanco et al, 2021;Sanchez-Gonzalez et al, 2022). In a two-part clinical study conducted by our team, ACCROS-I, and ACCROS-II, suggested that CPM intranasal-administered is an effective early intervention to reduce symptoms and accelerate clinical recovery in COVID-19 patients (Valerio-Pascua et al, 2022). Results showed that there were less hospitalization and severe cases.…”
Section: Molecular Docking Studiesmentioning
confidence: 90%